Communication networks on adopter farmers of planting technology at Cigasong districts in West Java - Rufaidah, Vivit Wardah; Suryana, Asep; Sugiana, Dadang; Sendjaja, Tuhpawana P. (Penerbit Universiti Kebangsaan Malaysia, 2020)
The process of adopting technology "Jarwo", in addition to the influence of external factors, is also influenced by internal factors, namely the structure of communication network. This research is ai med at analysing the structure of communication network and identifying the role of actors in the communication network of the farmers as the adopter of technology Jarwo. This research was conducted in Cigasong Subdistrict, West Java Province. Research method uses the survey method and data is analysed using communication network analysis. Population determination uses a nominalist approach. Sampling technique uses a small group of samples with a population of 131 farmers. Analysis uses a complete networks analysis consisting of three levels of measurement, i.e. actor level, system level and group level and data processing uses UCINET VI. The results of this research showed that: The structure of the communications network for the farmers adopting technology Jarwo has a low level of cohesiveness; the size of the network is relatively large; the level of tissue density is low; network structure is decentralised; and average distance between fellow actors is quite high, and actors who play an important role in "event information sources" Jarwo is actor #62 (agricultural extension) and #42 who are farmers as betweenness; on "Discussion Events" Jarwo, actor #235 who is an actor with centrality levels and high betweenness. This shows that the farmers adopting technology Jarwo prefer to discuss technology Jarwo with fellow farmers and informant neighbours.